Mekanisme Hujan Asam dan Dampak bagi Kehidupan - Putri, Mah Citra Yunia Artika; Sudarti, Sudarti; Yushardi, Yushardi (Peneliti.net, 2025)
Acid rain is a global environmental problem that is always a hot topic. Acid rain occurs when gases produced from burning motor vehicle fuel and natural activities such as carbon dioxide (CO2) and carbon monoxide (CO) react with water vapor (H2O) which has been mixed with other compounds from the evaporation process. This reaction produces carbonic acid (H2CO3), which is a type of weak acid. In addition, gases produced from burning or heating sulfur, such as hydrogen sulfide (H2S) and sulfur oxide (SO2), will react with water vapor (H2O) to form sulfuric acid (H2SO4), which is a type of strong acid. The problems that arise due to acid rain make researchers flock to find solutions to this acid rain. In this article the author will discuss various solutions that can be applied to overcome the impacts caused by acid rain. By studying appropriate and reliable literature, the author has prepared an article that will contain the impacts and solutions that must be applied to solve the problems caused by acid rain.